2008
DOI: 10.1103/physrevlett.100.017209
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Griffiths Phase in the Itinerant Magnetic SemiconductorFe1xCoxS2

Abstract: Critical points that can be suppressed to zero temperature are interesting because quantum fluctuations have been shown to dramatically alter electron gas properties. Here, the metal formed by Co doping the paramagnetic insulator FeS2, Fe1-xCoxS2 is demonstrated to order ferromagnetically at x > xc = 0.01+/-0.005, where we observe unusual transport, magnetic, and thermodynamic properties. We show that this magnetic semiconductor undergoes a percolative magnetic transition with distinct similarities to the Grif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 34 publications
(25 reference statements)
6
56
1
Order By: Relevance
“…2͒. M of the films with x = 0.2 and 0.3 is comparable to, but slightly larger than, the bulk M at low T from previous experiments that indicated, and band structure calculations supported, 17 disordered ferromagnetic metals such as Fe 1−x Co x S, 18 and is further supported by the difference between ZFC and FC data of Fig. 3.…”
supporting
confidence: 70%
“…2͒. M of the films with x = 0.2 and 0.3 is comparable to, but slightly larger than, the bulk M at low T from previous experiments that indicated, and band structure calculations supported, 17 disordered ferromagnetic metals such as Fe 1−x Co x S, 18 and is further supported by the difference between ZFC and FC data of Fig. 3.…”
supporting
confidence: 70%
“…The same experimental approach may also be useful in exploring the origin of similar logarithmic terms in the low-temperature resistivities of a variety of bulk systems. [21][22][23][24][26][27][28][29][30] In contrast to bulk solid solutions, the CaMnO 3 -CaRuO 3 superlattices have the advantage that the contact between the itinerant charge carriers and the magnetic scattering centers is limited to well-defined interfaces. Tailoring of spin textures at these interfaces may therefore open up new perspectives for functional oxide devices.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the weak hysteresis and absence of saturation of the MR is consistent with the magnetic field dependence of the net Mn magnetic moment in the magnetically ordered state. 17 Logarithmic terms in the temperature dependent resistivity have been reported for a wide variety of bulk materials within or close to magnetically ordered phases, including some heavyfermion systems, 26 cuprate superconductors above their crit- ical magnetic fields, 27-29 magnetic semiconductors such as Fe 1−x Co x S 2 , 30 and CaRu 1−x Mn x O 3 solid solutions, [21][22][23][24] but the interpretation of these effects is still under debate. In the latter systems, Kondo scattering due to antiferromagnetic interactions between conduction electrons and localized Mn spins has been invoked to explain this behavior.…”
Section: A DC Transportmentioning
confidence: 99%
“…Although some headway in this direction has been made, the complexity of disordered materials with strong interactions makes magnetic semiconductors difficult to model and understand 9,10,11 . In a recent paper we presented the results of an exploration into the magnetic and electronic properties of one such magnetic semiconducting compound, Fe 1−x Co x S 2 based on the diamagnetic insulating parent compound iron pyrite (FeS 2 ) 12 . We found that the insulator-tometal transition that occurs for low concentrations of Co doping was followed by a transition from a paramagnet to a disordered ferromagnet first apparent for small dopant concentrations, x, at very low temperatures.…”
Section: Introductionmentioning
confidence: 99%